2021
DOI: 10.1021/acsami.1c09650
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Direct Z-Scheme Heterojunction NiFe-Layered Double Hydroxide (LDH)/Zn0.5Cd0.5S for Photocatalytic H2 Evolution

Abstract: It is of great significance to construct heterojunctions using industrially produced co-catalysts. The direct Z-scheme composite photocatalyst provides an effective separation of photogenerated carriers. Herein, a kind of novel 2D/3D direct Z-scheme NiFe-LDH/Zn 0.5 Cd 0.5 S is prepared. Compared with fresh catalysts, the NiFe-layered double hydroxide (LDH)/Zn 0.5 Cd 0.5 S composite exhibits advantages including excellent visible light response ability and photoelectric performance and improved H 2 evolution ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 46 publications
(94 reference statements)
3
33
0
Order By: Relevance
“…The single-wavelength photocurrent tests were also employed to investigate the photogenerated-carrier transfer and separation. The optical absorption band gap (E g ) of g-C 3 N 4 and OTh 5 can be determined from a plot of (αhγ) 2 versus hγ based on their UV−vis DRS spectra (Figure S18), which are 2.70 and 2.00 eV, respectively. So the optical absorption thresholds of g-C 3 N 4 and OTh 5 are determined to be about 460 and 620 nm according to the equation λ = 1240/ E g .…”
Section: Mechanism Discussionmentioning
confidence: 99%
“…The single-wavelength photocurrent tests were also employed to investigate the photogenerated-carrier transfer and separation. The optical absorption band gap (E g ) of g-C 3 N 4 and OTh 5 can be determined from a plot of (αhγ) 2 versus hγ based on their UV−vis DRS spectra (Figure S18), which are 2.70 and 2.00 eV, respectively. So the optical absorption thresholds of g-C 3 N 4 and OTh 5 are determined to be about 460 and 620 nm according to the equation λ = 1240/ E g .…”
Section: Mechanism Discussionmentioning
confidence: 99%
“…108 On account of the research on LDHs and Zn x Cd 1−x S, Zn 0.5 Cd 0.5 S with a hollow polyhedral structure using ZIF-8 as a precursor was prepared first, and then, NiFe-LDH/Zn 0.5 Cd 0.5 S(LDH/ZCS) hollow polyhedron was synthesized successfully by anchoring NiFe-LDH to the surface of Zn 0.5 Cd 0.5 S using a hydrothermal method. 109 (Figure 14a). It is clearly observed that Zn 0.5 Cd 0.5 S is a surface rough polyhedron with NiFe-LDH thin nanosheets loaded on the surface of Zn 0.5 Cd 0.5 S as shown in Figure 14b,c.…”
Section: Momentioning
confidence: 99%
“…Among them, CdS-based catalysts are relatively efficient semiconductor photocatalysts for hydrogen production. , ZnS exhibits a more negative conduction band (CB) potential and stronger reduction reaction ability. When the Zn x Cd 1– x S solid solution is formed between CdS and ZnS, the band gap can be modulated by varying the Zn/Cd ratio, further affecting its application in photocatalytic decomposition of water . Further, Zn x Cd 1– x S is considered to be one of the most promising photocatalysts .…”
Section: Introductionmentioning
confidence: 99%
“…When the Zn x Cd 1−x S solid solution is formed between CdS and ZnS, the band gap can be modulated by varying the Zn/Cd ratio, further affecting its application in photocatalytic decomposition of water. 24 Further, Zn x Cd 1−x S is considered to be one of the most promising photocatalysts. 25 Various morphological Zn x Cd 1−x S have already been prepared, including nanoparticles, 26,27 quantum dots, 28 nanosheets, 29 nanorods, 30 and nanocages.…”
Section: Introductionmentioning
confidence: 99%